2022
DOI: 10.1186/s13068-022-02200-3
|View full text |Cite
|
Sign up to set email alerts
|

An engineered non-oxidative glycolytic bypass based on Calvin-cycle enzymes enables anaerobic co-fermentation of glucose and sorbitol by Saccharomyces cerevisiae

Abstract: Background Saccharomyces cerevisiae is intensively used for industrial ethanol production. Its native fermentation pathway enables a maximum product yield of 2 mol of ethanol per mole of glucose. Based on conservation laws, supply of additional electrons could support even higher ethanol yields. However, this option is disallowed by the configuration of the native yeast metabolic network. To explore metabolic engineering strategies for eliminating this constraint, we studied alcoholic fermentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 77 publications
2
17
1
Order By: Relevance
“… Deng et al (2022) optimized a cascade system by regulating the intensity of NADPH gene expression to produce a higher (S)-equol titer (3418.5 mg/L) with a conversion rate of approximately 85.9%. van Aalst et al (2022) functional expression of the gene in anaerobic, slow-growing chemostat cultivation on glucose-sorbitol mixtures resulted in a 12-fold higher co-consumption rate of sorbitol than that observed in sorbitol-consuming reference strains. Rami Reddy Tadi et al (2021) metabolic engineering of Bacillus megaterium through co-expression of the precursor ( phbRBC ) and NADPH cofactor regeneration ( zwf ) genes resulted in a 2.67-fold increase in PHB accumulation.…”
Section: Regulation Of Cofactor Metabolic Balance and Its Applicationmentioning
confidence: 84%
“… Deng et al (2022) optimized a cascade system by regulating the intensity of NADPH gene expression to produce a higher (S)-equol titer (3418.5 mg/L) with a conversion rate of approximately 85.9%. van Aalst et al (2022) functional expression of the gene in anaerobic, slow-growing chemostat cultivation on glucose-sorbitol mixtures resulted in a 12-fold higher co-consumption rate of sorbitol than that observed in sorbitol-consuming reference strains. Rami Reddy Tadi et al (2021) metabolic engineering of Bacillus megaterium through co-expression of the precursor ( phbRBC ) and NADPH cofactor regeneration ( zwf ) genes resulted in a 2.67-fold increase in PHB accumulation.…”
Section: Regulation Of Cofactor Metabolic Balance and Its Applicationmentioning
confidence: 84%
“…This phenomenon has been reported in genetically modified S. cerevisiae strains capable of fermenting sorbitol under anaerobic conditions . While analogous strategies for xylitol are not (yet) documented, they could potentially favor the strategy of solubilizing xylose and reducing it to xylitol during RCF, given the higher theoretical ethanol yields.…”
Section: Resultsmentioning
confidence: 99%
“…In industrial ethanol fermentation, the specific growth rate decreases as the ethanol concentration reaches inhibitory levels and/or non-sugar nutrients are depleted (16). A recent study showed that, in slow-growing anaerobic chemostat cultures (0.05 h -1 ), a PRK-RuBisCO strain produced up to 80-fold more acetaldehyde and 30-fold more acetate than a reference strain (17). This production of acetaldehyde and acetate was attributed to an in vivo overcapacity of the key enzymes of the PRK-RuBisCO bypass.…”
Section: Introductionmentioning
confidence: 99%
“…This production of acetaldehyde and acetate was attributed to an in vivo overcapacity of the key enzymes of the PRK-RuBisCO bypass. Reduction of the copy number of the expression cassette for RuBisCO led to lower acetaldehyde and acetate production in slow-growing cultures and a corresponding increase in ethanol yield (17). The production of acetaldehyde and acetate was further decreased by reducing PRK activity by lowering protein abundance by a C-terminal extension of PRK, or by expressing the spinach prk gene from the growth-rate-dependent ANB1 promoter (17,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation